Experimentação de química no ensino médio: percepções e concepções de alunos e professores - Zimmer, Geórgia Cristiane; Folmer, Vanderlei; Regina Bonini Marzari, Mara; Colman Espíndola Lima, Quelen (Góndola, enseñanza y aprendizaje de las ciencias, 2021)
This work aimed to investigate the perception and conception of teachers and students in the experimentation of Chemistry, in High School, at a technical college integrated. To achieve the purpose, an interview was conducted with the two Chemistry teachers and applied a questionnaire to students in the third year of high school. Through the teacher's interview, we could evidence the lack of a laboratory technician and the low course load of the discipline difficult to carry out experimental classes. Regarding the students' answers, we found that they like the theoretical and experimental Chemistry classes, given that through experimentation they can correlate theory with practice. This result, may answer back to the teaching method, and also due the school has an equipped Chemistry laboratory, the reason why, when possible, experimental Chemistry classes are carried out. This work shows that, even in an equipped technical school, there are still other factors that hinder the frequency of practical classes in the Chemistry laboratory. In order to deepen the studies carried out, further investigation is needed as to how these listed factors directly affect teaching, involving a greater number of schools. In addition, it is important to assess how changes in the teaching method directly influence the learning of Chemistry.